2021
DOI: 10.3390/nano11071837
|View full text |Cite
|
Sign up to set email alerts
|

pH Sensitive Dextran Coated Fluorescent Nanodiamonds as a Biomarker for HeLa Cells Endocytic Pathway and Increased Cellular Uptake

Abstract: Fluorescent nanodiamonds are a useful for biosensing of intracellular signaling networks or environmental changes (such as temperature, pH or free radical generation). HeLa cells are interesting to study with these nanodiamonds since they are a model cell system that is widely used to study cancer-related diseases. However, they only internalize low numbers of nanodiamond particles very slowly via the endocytosis pathway. In this work, we show that pH-sensitive, dextran-coated fluorescent nanodiamonds can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It is also possible that a small part of the FNDs escaped from endosomes into the cytoplasm but did not translocate into lysosomes. Similar cases have been reported in some studies. , …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is also possible that a small part of the FNDs escaped from endosomes into the cytoplasm but did not translocate into lysosomes. Similar cases have been reported in some studies. , …”
Section: Resultssupporting
confidence: 92%
“…Similar cases have been reported in some studies. 40,41 For the PLA-FND group, the colocalization proportion of PLA-FNDs internalized at early endosomes is similar to FNDs. But, unlike FNDs, the proportion of PLA-FNDs colocalized with late endosomes or lysosomes, and LMAP-1 marked decreases significantly with incubation time.…”
Section: ■ Materials and Methodsmentioning
confidence: 85%
“…Recently, it was shown that only a modest number of ND enter through the endocytosis pathway; in fact, fluorescent ND can be also internalized via endolysosomes and finally excreted from the cells. 49 We have performed clonogenic and wound healing assays to verify the anti-cancer efficacy of our strategy. Colony analysis after treatment with ND-PEI-miR-34a showed a decrease in the tumorigenic potential of breast cancer cell lines if compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated cell internalization of NDs through fluorescence imaging of NV centers of NDs. 168…”
Section: Specific Functionalizationsmentioning
confidence: 99%